Contribution of Galileo to search and rescue - (:unkn) unknown (My University, 2005)
Galileo, the European Global Navigation Satellite System is expected to take its place in near future, alongside other satellite navigation systems. There is no doubt that with its superior properties it will enhance the usage of satellite aid in everyday life. One very important aspect of Galileo among its benefits is the Search and Rescue service. This feature will complement the Cospas-Sarsat, Search and Rescue satellite system, with its accuracy, additional properties like return link feature, near real time reception of distress alerts, increased coverage and availability, integrity and other technological innovations. Fulfilling the gap between Cospas-Sarsat LEO and GEO satellites with Galileo's MEO Satellites will obviously increase the effectiveness of Cospas-Sarsat system. In this paper "Contribution of Galileo to Search and Rescue" is presented by reviewing both Cospas-Sarsat and Galileo systems. The main purpose of the paper is to draw attention of academical, commercial, governmental and civil societies to Search and Rescue aspects of Galileo as related to Cospas-Sarsat. We also hope it promotes cooperation and synergy among societies and countries about the humanitarian efforts of search and rescues on a non-discriminatory basis. © 2005 IEEE.
Keywords: Beacon; Cospas-Sarsat; Galileo; GEO; GNSS; ICAO; IMO; LEO; MEO; Navigation; Satellite; Search and Rescue (SAR)